Effect of Financial Performance on the Effectiveness of Financial Technology (FinTech) Collaboration at Bank Syariah Indonesia with Liquidity as a Moderating Variable - Qisthoni Permatasari; Wuryaningsih Dwi Lestari; Mutia Kemala Hidayat (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of financial performance on the effectiveness of financial technology (fintech) collaboration at Bank Syariah Indonesia (BSI), with liquidity as a moderating variable. This research employs a quantitative approach using secondary data from BSI’s quarterly financial reports for the period 2021–2024. Financial performance is measured by Net Operating Margin (NOM) and operational efficiency by the Operational Cost to Operating Income ratio (BOPO), while liquidity is proxied by the Financing to Deposit Ratio (FDR). The effectiveness of fintech collaboration is measured through digital transaction growth and mobile banking usage. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that financial performance and operational efficiency have a significant effect on the effectiveness of fintech collaboration. Liquidity strengthens the relationship between financial performance and fintech collaboration effectiveness. These findings highlight the importance of maintaining sound financial performance and liquidity to optimize fintech collaboration in Islamic banking.